CD103+ tumor-infiltrating lymphocytes are tumor-reactive intraepithelial CD8+ T cells associated with prognostic benefit and therapy response in cervical cancer. - Komdeur, F; Prins, T; van de Wall, S; Plat, A; Wisman, G; Hollema, H; Daemen, T; Church, D; de Bruyn, M; Nijman, H (Taylor and Francis, 2017)
Human papilloma virus (HPV)-induced cervical cancer constitutively expresses viral E6/E7 oncoproteins and is an excellent target for T cell-based immunotherapy. However, not all tumor-infiltrating T cells confer equal benefit to patients, with epithelial T cells being superior to stromal T cells. To assess whether the epithelial T cell biomarker CD103 could specifically discriminate the beneficial antitumor T cells, association of CD103 with clinicopathological variables and outcome was analyzed in the TCGA cervical cancer data set (n = 304) and by immunohistochemistry (IHC) in an independent cohort (n = 460). Localization of CD103+ cells in the tumor was assessed by immunofluorescence. Furthermore, use of CD103 as a response biomarker was assessed in an in vivo E6/E7+ tumor model. Our results show that CD103 gene expression was strongly correlated with cytotoxic T cell markers (e.g. CD8/GZMB/PD1) in the TCGA series. In line with this, CD103+ cells in the IHC series co-expressed CD8 and were preferentially located in cervical tumor epithelium. High CD103+ cell infiltration was strongly associated with an improved prognosis in both series, and appeared to be a better predictor of outcome than CD8. Interestingly, the prognostic benefit of CD103 in both series seemed limited to patients receiving radiotherapy. In a preclinical mouse model, HPV E6/E7-targeted therapeutic vaccination in combination with radiotherapy increased the intratumoral number of CD103+ CD8+ T cells, providing a potential mechanistic basis for our results. In conclusion, CD103 is a promising marker for rapid assessment of tumor-reactive T cell infiltration of cervical cancers and a promising response biomarker for E6/E7-targeted immunotherapy.